2003
DOI: 10.1002/ejoc.200200662
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Saturated 5H‐Pyrrolo[1,2‐a][3,1]benzoxazin‐1(2H)‐ones Prepared from 4‐Oxopentanoic Acid and Cyclic Amino Alcohols

Abstract: Saturated heterocycles containing two condensed heterocyclic rings and a carbo(bi)cyclic ring have been prepared by the reaction of 4-oxopentanoic acid (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Apart from this property, enantiopure amino alcohols are also important derivatives for the synthesis of various chemical compounds. They constitute convenient starting materials for the synthesis of various 1,3-heterocycles for example (Ager et al 1996;Fülöp et al 1997;Gyonfalvi et al 2003;Kivelä et al 2003Kivelä et al , 2005. Although 1,2-amino alcohols have received much attention because they are generally readily accessible in enantiomerically pure form from natural precursors (Gyonfalvi et al 2003;Reetz et al 1987;Delair et al 1994;Masui and Shiori 1998;Laczkowski et al 2009;, the synthesis and the use of chiral 1,3-amino alcohols are still undergoing development and remain a challenge (Lait et al 2007;Didier et al 1991; Barluenga et al 1993; Bartoli et al 1994;Kossenjans and Martens 1999;Kochi et al 2003;Raghavan et al 2004;Murai et al 2005;Balazs et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this property, enantiopure amino alcohols are also important derivatives for the synthesis of various chemical compounds. They constitute convenient starting materials for the synthesis of various 1,3-heterocycles for example (Ager et al 1996;Fülöp et al 1997;Gyonfalvi et al 2003;Kivelä et al 2003Kivelä et al , 2005. Although 1,2-amino alcohols have received much attention because they are generally readily accessible in enantiomerically pure form from natural precursors (Gyonfalvi et al 2003;Reetz et al 1987;Delair et al 1994;Masui and Shiori 1998;Laczkowski et al 2009;, the synthesis and the use of chiral 1,3-amino alcohols are still undergoing development and remain a challenge (Lait et al 2007;Didier et al 1991; Barluenga et al 1993; Bartoli et al 1994;Kossenjans and Martens 1999;Kochi et al 2003;Raghavan et al 2004;Murai et al 2005;Balazs et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Syntheses of chiral oxopyrrolooxazoles and compounds containing quaternary carbon centres have also been described. [11Ϫ14] The preparation of methanooxopyrrolo [1,2-a] [3,1]benzoxazines from 1 by reaction with cyclic amino alcohols was recently reported; [15] this work fits into the frame of our studies on oxocarboxylic acids, [16,17] in which the versatility of the starting materials was confirmed by the synthesis of new types of fused heterocyclic systems. In the continuation of this work, interesting results were obtained by condensation of 1 with the di-endo-and di-exo-amino acids 2؊5.…”
Section: Introductionmentioning
confidence: 53%
“…18 In particular, their simple reduction allowed the preparation of chiral cyclic 1,3-amino alcohols that can be used as ligands in asymmetric reactions [19][20][21] or as convenient starting materials for the synthesis of various 1,3-heterocycles. [22][23][24] In this context, synthesis of new sterically constrained enantiomerically pure cyclic amino acids is particularly attractive. We have previously found that the chiral nitroacrylate (S)-or (S)-2 was an efficient dienophile to prepare enantiopure trans-b-norbornane amino acids by reacting with cyclopentadiene.…”
Section: Introductionmentioning
confidence: 99%